Tunnelling Management by Design - Muir Wood, Alan (Taylor & Francis, 2000)
Tunnelling has become a fragmented process, excessively influenced by lawyers'notions of confrontational contractual bases. This prevents the pooling of skills, essential to the achievement of the promoters' objectives. Tunnelling: Management by Design seeks the reversal of this trend. After a brief historical treatment of selected developments, th